Unsilencing the Student Voice: Detecting and Addressing ChatGPT-Generated Texts Presented as Student-Authored Texts at a University Writing Centre - Zonnike Coetzer; Peet van Aardt (International Journal of Critical Diversity Studies)
The convergence of ChatGPT and other artificial intelligence writing tools at tertiary learning institutions has raised concerns for lecturers and academic practitioners, particularly regarding the significant impact that overreliance on these tools can have on students’ development of critical thinking and academic integrity ( Lo, 2023 , p. 420). The greatest concern—according to the authors of this article—seems to be the possible loss of the student voice and academic opinion. This is because of the evident increase in students who submit AI-generated texts as their own ( McDade, 2023 ). In the African context, where the critical voice of student scholars is extolled as one of the main spearheads for decolonialisation ( Charles, 2019 , p. 8), this erasure of the student voice through the overreliance on AI is particularly disconcerting. Therefore, the researchers propose and discuss strategies to be used in university classrooms and writing centres to determine if a text is AI-generated and to reinvite students to formulate their own academic opinions and, therefore, reclaim their own critical academic voice. In addition, techniques to promote fundamental learning skills that can be implemented by lecturers and writing centre consultants will be explored. Approaching the topic from the perspective of university writing centre practitioners, one of the research goals is to raise awareness of the characteristics and limitations of AI-generated texts to distinguish these writings from student-written texts. This will be done by juxtaposing examples of both—highlighting characteristics like (lack of) creativity, (un)reliability of citations, cohesion, sentence length and consistency. The text analyses will provide readers with relatable examples to assist them in identifying the lack of student voice. Finally, the researchers will explore how the merging of Critical Theory, socio-constructivism, and Socratic questioning techniques, as proposed by Argendien, Pillay, Dube and Masinga (2022, p. 69), can be implemented in the University of the Free State’s Writing Centre and Academic Literacy Unit, in order to encourage students who overly relied on AI to regain their agency as academic writers.